The experiences of nurse educators in implementing evidence-based practice in teaching and learning - Gloria N. Mthiyane; Debbie S. Habedi (AOSIS, 2018)
Background: Nurse educators have a vital role to mentor student nurses in relation to developing evidence-based practice (EBP) skills, accessing research products and participating in research projects. This requires more innovative teaching approaches that promote active participation, creativity and critical thinking in students such as online teaching and learning, accessing electronic resources, video conferencing and research-based teaching and learning. Aim: To determine the nurse educators' experiences in implementing EBP in teaching and learning, and to describe the importance and benefits of EBP teaching and learning to the nursing profession, especially for nurse educators and student nurses. Setting: Two chosen campuses from Umgungundlovu Health District under the KwaZulu-Natal College of Nursing (KZNCN) and offering a 4-year R425 training programme. Methods: Qualitative research design and methods were followed in conducting the study. A non-probability purposive sampling technique was used to access the sample of 12 nurse educators. Data were collected using semi-structured interviews, the interview guide, and the digital voice recorder. Results: Data were analysed manually, following a content thematic approach and two themes emerged as challenges experienced by nurse educators with the implementation of EBP in teaching and learning and benefits and value of EBP in teaching and learning. Findings revealed that, although most of the nurse educators are supportive and displayed a positive attitude towards implementing EBP in teaching and learning, the level of knowledge and skills was questionable. This was coupled with a lack of motivation and commitment towards research. Conclusions: Evidence-based practice has an essential potential role to play through incorporating more practice-based evidence of nurse educators in teaching and learning implementation. The nurse educators should use EBP to ensure that student nurses receive high-quality nursing education.